Zinc in microscopic calcifications isolated from thyroid fine needle aspiration may serve as a biomarker of thyroid nodule malignancy: A promising proof-of-concept. (15th April 2023) - Gotnayer, Lotem; Aranovich, Dina; Fraenkel, Merav; Yoel, Uri; Vidavsky, Netta
Abstract: Thyroid nodules (TNs) are common neck ultrasonography (US) findings, yet only 5-10% of these nodules harbor thyroid cancer (TC). When US characteristics are consistent with an intermediate or high suspicion for TN malignancy, fine needle aspiration for cytology (FNAC) is indicated. The main limitation of FNAC is that cytological results can be indeterminate in up to 30% of cases, necessitating reevaluation through repeated FNAC, expensive molecular testing, or diagnostic thyroid lobe resection. As such, there is a need for further refinement of current diagnostic algorithms for TNs without subjecting patients to additional invasive procedures. As calcifications detected during thyroid US are considered a high-risk feature for malignancy, we used the material remaining following routine thyroid FNAC to isolate microscopic calcifications (MCs). We then characterized the elemental composition, morphology, and crystal phases of these MCs, ultimately revealing differences between the MCs from benign and malignant TNs. Specifically, thyroid MCs were identified as calcium phosphate crystals containing varying levels of magnesium, sodium, iron, and zinc. MCs obtained from malignant TNs, mainly papillary thyroid carcinoma, were composed of sub-micrometer spherical particles, whereas MCs from benign TNs consisted of faceted particles. While samples from most patients with a final diagnosis of malignant TNs (50% of them with indeterminate cytology) harbored zinc-containing MCs, zinc was largely absent in MCs from benign TNs (23% with indeterminate or non-diagnostic cytology). Together, these data suggest that the presence of zinc in MCs isolated from samples collected during routine FNAC may potentially offer value as a biomarker of TN malignancy. Statement of significance: As up to 40% of patients assessed for thyroid malignancy do not receive a definite diagnosis following thyroid nodule (TN) fine needle aspiration (FNA), there is a pressing need to improve the accuracy of current diagnostic algorithms. Chemical analyses of microscopic calcifications (MCs) may serve as a diagnostic target. We developed a straightforward protocol to chemically characterize MCs from excess material collected from TNs during routine FNA and found that these MCs differed between benign and malignant TNs. Specifically, zinc in TN-derived MCs may indicate a higher nodule malignancy risk, thus increasing the diagnostic accuracy of the FNA procedure, reducing the need for recurrent biopsies and diagnostic surgical procedures, and decreasing the costs, uncertainty, and stress faced by affected patients. Graphical Abstract: Image, graphical abstract